2013
DOI: 10.1016/j.yhbeh.2013.02.018
|View full text |Cite
|
Sign up to set email alerts
|

The development of psychotic disorders in adolescence: A potential role for hormones

Abstract: The notion that adolescence is characterized by dramatic changes in behavior, and often by emotional upheaval, is widespread and longstanding in popular western culture. In recent decades, this notion has gained increasing support from empirical research showing that the peri- and post-pubertal developmental stages are associated with a significant rise in the rate of psychiatric symptoms and syndromes. As a result, interest in adolescent development has burgeoned among researchers focused on the origins of sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 155 publications
0
34
0
1
Order By: Relevance
“…It has been proposed that the adverse effects of stress exposure on vulnerable individuals are partially mediated by the consequent increase in activation of the hypothalamic pituitary-adrenal (HPA) axis and elevated cortisol secretion (Walker et al, 2008). In addition, independent of stress, there is evidence that normal neuromaturational processes augment stress and cortisol levels during adolescence, and it has been suggested that these processes increase risk for onset of the prodrome to serious mental disorders, including psychosis (Trotman et al, 2013; Walker et al, 2008). Specifically, the risk for psychosis onset rises dramatically following age 13, and increases with each year of age through adolescence (de Girolamo et al, 2012; Thorup at al., 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proposed that the adverse effects of stress exposure on vulnerable individuals are partially mediated by the consequent increase in activation of the hypothalamic pituitary-adrenal (HPA) axis and elevated cortisol secretion (Walker et al, 2008). In addition, independent of stress, there is evidence that normal neuromaturational processes augment stress and cortisol levels during adolescence, and it has been suggested that these processes increase risk for onset of the prodrome to serious mental disorders, including psychosis (Trotman et al, 2013; Walker et al, 2008). Specifically, the risk for psychosis onset rises dramatically following age 13, and increases with each year of age through adolescence (de Girolamo et al, 2012; Thorup at al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Also, independent of stress exposure, the normative rise in cortisol during adolescence may increase susceptibility to psychiatric disorders in vulnerable individuals (Quevedo et al, 2009; Sontag-Padilla et al, 2012). It has been suggested that increased HPA activation following the onset of puberty may increase susceptibility for a range of psychiatric syndromes, including psychosis (Trotman et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Pubertal hormones play a significant role in psychological change in adolescence: Extreme variations in the onset (timing) of pubertal development are linked to risks for depression and externalizing behavior problems (for reviews, see Ge and Natsuaki 2009; Graber 2013; Negriff and Susman 2011); attainment of midpubertal status appears to increase normative changes in risky behavior and to trigger psychopathology in vulnerable individuals (e.g., Gunnar et al 2009; Trotman et al 2013). These changes are hypothesized to reflect effects of social responses to youths’ changing bodies, and sex hormones and social experiences acting on the developing brain and stress systems.…”
Section: Introductionmentioning
confidence: 99%
“…There is a long-standing interest in psychological consequences of variations in pubertal development, particularly elevated risks of early maturation in girls for depression and externalizing behavior problems (e.g., delinquency, substance use, early sexual activity; for reviews, see Ge & Natsuaki, 2009; Graber, 2013; Negriff & Susman, 2011). Recent work has highlighted the role of puberty in normative adolescent development (e.g., increased risk taking), and in triggering psychopathology in vulnerable individuals; these changes are hypothesized to reflect effects of sex hormones and social experiences acting on the developing brain and stress systems (e.g., Gunnar, Wewerka, Frenn, Long, & Griggs, 2009; Trotman et al, 2013). …”
mentioning
confidence: 99%